Sustainable technology selection decision-making model for enterprise in supply chain: Based on a modified strategic balanced scorecard. (10th January 2017) - Xia, De; Yu, Qian; Gao, Qinglu; Cheng, Guoping
Abstract: During technology adoption, assessment of its sustainable character is a difficult task due to limited insight and the various dimensions of sustainability, as well as its complicated application at the operational level. A proper decision-making framework and method may be conducive to bridging generic and macro-level sustainability with local-site and task-oriented technology selection, improving the application of sustainable technology. For this reason, a framework is explored to highlight the sustainable nature of relevant components during an operational decision-making process within the supply chain. With an eye to the triple bottom of sustainability, the product chain, value-added activities of supply chain and stakeholders are analyzed and embedded into the technology selection method. The dynamic relationships among these components (product chain, value-added activities and stakeholders) as carriers of technology are also discussed so as to investigate their sustainable features. Furthermore, to figure out the whole technology decision-making logic map, a modified strategic balanced scorecard is established and applied to evaluate technology candidates in terms of their features of sustainability. Next, a computing method is designed to produce a sustainable technology choice. The multilateral mechanisms among the three groups, as well as within each group, during the technology selection process are identified and elaborated completely. The framework of analysis and method presented in the paper add insight to sustainability theoretically, and guide its application in technology adoption. Managerial implications, as well as limitations of this work, are concluded at the end of this paper. Highlights: Sustainable nature of sections in supply chain is explored for technical adoption. The essential assessment framework and factors are established. A method with modified balanced scorecard is designed for technical adoption. A correlation mechanism influences the technical performance in supply chain.